An Analysis of Students’ Perceptions about The Efficiency of Using of Zoom Cloud Meeting for Online Learning During Pandemic Covid-19 - Amatul Mughis Mahabbah (Graduate Program, University of Islam Malang, 2021)
The purpose of this study were to determine the efficiency of the zoom cloud meeting application in online learning as an alternative solution in the era of the Covid-19 pandemic. The subjects of this study were thirty of English students of the fourth, sixth, and eighth semester at University of Islam Malang. The research was qualitative research. The data collection technique was carried out by giving questionnaires through Google Form and interviews using WhatsApp to thirty students at the Islamic University of Malang. The data were analyzed and interpreted through qualitative procedure. The findings indicate that the students have positive perceptions about the efficiency of the use of Zoom Cloud Meeting Application as an alternative solution in online learning in the pandemic Covid-19. The results of this study indicate that the use of the Zoom Cloud Meeting application makes it easy for teachers and learners to be able to do face-to-face learning. although learning is done online and all users are in different places.